Synthesis and characterization of crosslinked carboxymethyl sago starch / citric acid hydrogel and its absorption properties for Pb(II), Cu(II), Ni(II) and Zn(II) ions in aqueous solutions - Keirudin, Amyrah Auni (2019)
Heavy metal pollution is a serious environmental issue being faced around the world. To overcome this problem, sorption procedure was chosen as an effective method to remove heavy metal in wastewater treatment. Carboxymethyl sago starch (CMSS), a modified biopolymer gains much attention because of it is low cost and environmental friendly. Moreover, it possesses functional groups such hydroxyl and carboxyl, which give advantage for crosslinking reaction to form water-insoluble hydrogel. The main objective of this study was to synthesize CMSS hydrogels by crosslinking with citric acid and then applied as metal sorbent to overcome excessive heavy metal pollution. In preparation of CMSS/CA hydrogel, the effect of concentration of CMSS, concentration of citric acid, curing time and temperature on gel content were studied. The optimum conditions for preparation of CMSS/CA hydrogel were; 60% w/v of CMSS, 10% w/w of citric acid, 48 hours of curing time at 50°C curing temperature. The CMSS/CA hydrogel was characterized by Fourier-transform infrared (FT-IR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and X-ray diffraction (XRD). The absorption band at 1726 cm-1 observed in the FT-IR spectrum of CMSS/CA hydrogel indicated the carboxylic acid and ester bonds formed from the reaction of citric acid with hydroxyl group of CMSS. Besides, the crosslinkages in the CMSS/CA hydrogel increased the thermal stability of CMSS and the presence of various size of pores also can be seen from the SEM micrograph. The removal of heavy metal lead (II), copper (II), zinc (II) and nickel (II) ions from aqueous solution was analysed using inductively coupled plasma optic emission spectrometry (ICP-OES). The effects of pH metal solution, reaction time, initial concentration metal ions and reaction temperature on the sorption capacity and removal percentage were investigated. From the results, the sorption capacity of Pb2+, Cu2+, Ni2+ and Zn2+ onto CMSS/CA hydrogel were 64.48, 36.56, 16.21, 18.45 mg/g, respectively. Meanwhile, the removal percentage of Pb2+, Cu2+, Ni2+ and Zn2+ from aqueous solution were 91.97, 56.43, 34.30, 40.08%, respectively. All heavy metal ion sorption followed pseudo-second order kinetic model and the isotherm data followed Langmuir model. The thermodynamic studies revealed that sorption process of Pb2+, Cu2+, Ni2+ and Zn2+ were spontaneous and exothermic in nature. The heavy metal removal experiment demonstrated that CMSS/CA hydrogel has high selectivity for Pb2+ in both non-competitive and competitive conditions. The electropositivity of Pb2+ made it more selective than Cu2+, Ni2+ and Zn2+ due to the ability of Pb2+ to donate electron and interact with active site of CMSS/CA hydrogel. The desorption percentage of Pb2+ from CMSS/CA hydrogel was 91.86% indicated that the metal ions were able to leach from the hydrogel efficiently and also an appropriate method to dispose sorbent in safer condition. In conclusion, this study showed that the CMSS/CA hydrogel has a potential to be used as a heavy metal sorbent that can beneficially reduce the heavy metal pollution.